Photocatalytic and Antibacterial Performance of α‐Fe2O3 Nanostructures. Issue 10 (7th April 2017) - Jana, T. K.; Pal, A.; Mandal, A. K.; Sarwar, S.; Chakrabarti, P.; Chatterjee, K.
Abstract: Morphology engineered α‐Fe2 O3 nanostructures with magnificent antibacterial property and excellent photocatalytic activity have been presented to address the long‐standing environment issue. After tuning the morphology via solvothermal route the products were characterized by morphological, structural and elemental analysis. The visible‐light photocatalytic activity of α‐Fe2 O3 nanostructures was evaluated by using them to degrade methylene blue (MB) dye under visible light irradiation in the presence of H2 O2 . Amidst the series, nano bead‐like structure exhibited the greatest activity toward MB degradation with 90 % degradation efficiency. Unique bead‐like structure having fluctuant diameter is thought to play a key role in the enhanced separation of electron‐hole pairs of α‐Fe2 O3 and results superior photocatalytic activity. On the other hand all the shape variants of α‐Fe2 O3 nanostructures showed brilliant antibacterial effect against Gram negative ( Escherichia coli ) bacterium. Based on the current findings, the presented α‐Fe2 O3 nanostructures with their superb photocatalysis and antibacterial activity can be a promising candidate for industry to abate the ever rising environmental threat. Abstract : Morphology engineered α‐Fe2 O3 nanostructures with magnificent photocatalytic activity and antibacterial property have been presented to address the long‐standing environment issue. The visible‐light photocatalytic activity of α‐Fe2 O3 nanostructures was evaluated by using them to degrade methylene blue (MB) dye under visible light irradiation in the presence of H2 O2 . Nano bead‐like structure exhibited the greatest activity with 90% degradation efficiency. On the other hand all the shape variants of α‐Fe2 O3 nanostructures showed brilliant antibacterial effect against Escherichia coli bacterium.